De la crise du roman: la poétique romanesque de la N.R.F. sur les pages de Nyugat - Radvánszky, Anikó (Verbum – Analecta Neolatina, 2011)
This paper examines the impact of history on aesthetics discourse that took place from the 1910s to the 1930s in the Hungarian journal Nouvelle Revue Française in the context of the novel as a genre. A primary resource are the writings of Albert Gyergyai in the journal Nyugat, which had been an important publisher of French literature and culture since the 1920s. Through examining Gyergyai's publications and his book A mai francia regény (The modern French novel), as well as the Hungarian reception of Gide (in which Gyergyai's works cited played a partial contributing role), the present study examines the extent to which the French genre-dispute, intimately linked to the quesions of literary modernism, was related to the literary renaissance associated with Nyugat.